Eight new species of Andrena Fabricius (Hymenoptera: Apoidea: Andrenidae) from Israel—a Mediterranean hotspot for wild bees - Pisanty, Gideon; Scheuchl, Erwin; Dorchin, Netta (Zootaxa, 2016)
More than 150 solitary bee species of the genus Andrena Fabricius are known from Israel and the West Bank, where they are distributed along a broad climatic gradient and diverse habitats and vegetation types. Extensive collecting throughout Israel in recent years has yielded eight new species and one new subspecies, adding to the rich bee fauna of the region:   A. crocusella Pisanty & Scheuchl n. sp., A. danini Pisanty & Scheuchl n. sp., A. hermonella Scheuchl & Pisanty n. sp., A. israelica Scheuchl & Pisanty n. sp., A. judaea Scheuchl & Pisanty n. sp., A. menahemella Scheuchl & Pisanty n. sp., A. palaestina Pisanty & Scheuchl n. sp., A. perahia Pisanty & Scheuchl n. sp., and A. sphecodimorpha mediterranea Pisanty & Scheuchl n. ssp. The previously unknown female of A. fimbriatoides Scheuchl 2004 and male of A. wolfi Gusenleitner & Scheuchl 2000 are also described here for the first time. The discovery of males of A. wolfi lead us to reinstate A. iohannescaroli Nobile 2000 as a valid taxon. Detailed morphological description and differential diagnosis against closest relatives are provided for all species, as well as information on the distribution, phenology and flower visitation, when available. A neotype is designated for A. sphecodimorpha Hedicke, the holotype of which is considered to be lost. Additional collecting efforts in diverse habitats and seasons, incorporating diverse collecting techniques, are required in order to deepen our knowledge of the rich bee fauna in threatened habitats in the Mediterranean Basin, which constitutes one of the world’s major hotspots for wild bees.